Jesus and Spirituality in Interreligious Perspectives - Martin, Nancy M. (Religions, 2022)
Rarely do members of diverse religions engaged in interreligious dialogue find agreement on metaphysics and doctrine, though such conversations may be very fruitful and lead to greater understanding and mutual illumination. In the area of religious experience, however, recognition of commonality may be much more readily apparent, and in such encounters, the life and spirituality of Jesus provide a meeting ground. This essay examines Jesus as a catalyst for spiritual inspiration and transformation from Islamic, Hindu, Buddhist and nontraditional perspectives. As an integral figure in Islam, Jesus appears in the writings of the likes of Ibn Arabi, Rumi and more contemporary Sufi teachers. Hindus and Buddhists, too, have embraced him, from Sri Ramakrishna and Gandhi to Thich Nhat Hanh. This essay will explore the integral role Jesus plays in such interreligious contexts, embodying self-sacrifice, wisdom and active love and interweaving personal transformation, contemplative practice and social engagement in the pursuit of liberating spiritual realization. In so doing, the essay will argue that such interreligious perspectives are an essential element in a full accounting of Jesus’ place in the spiritual lives of diverse human beings.